PERBEDAAN MODEL TEACHER CENTERED LEARNING DENGAN STUDENT CENTERED LEARNING TERHADAP KETERAMPILAN BERMAIN BULUTANGKIS - Eka Widyaningsih, - (2023)
ABSTRACT DIFFERENCES BETWEEN TEACHER CENTERED LEARNING AND STUDENT CENTERED LEARNING ON BADMINTON PLAYING SKILLS Eka Widyaningsih ekawidya3009@upi.edu Study program Physical Education Health and Recreation Indonesia University of Education Mentor I: Dr. Sucipto, M.Kes. AIFO Mentor II: Dr. Dr. Helmy Firmansyah, M.Pd. The application of learning models can have an impact on optimal badminton playing skills. This study aims to determine the difference between Teacher Centered Learning and Student Centered Learning on badminton playing skills. The method used in this study was an experiment with a two group pretest-posttest design. In taking the sample using saturated sampling technique, namely students who take part in extracurricular badminton as many as 40 students (20 students in the TCL group and 20 students in the SCL group). The instrument uses the Games Performance Assessment Instrument (GPAI) to measure skills in playing badminton. Data analysis used the Shapiro-Wilk test, Levene Statistics, Paired Sample T-Test and Independent Sample T-Test with the help of the SPSS 25 application. Based on data processing and analysis it was found that there was an effect on the SCL group (sig 0.000 <0.05), there was no effect on the TCL group (sig 0.862 > 0.05), and there was a difference in the effect between the TCL and SCL groups (difference = 1.39; sig 0.000 <0.05). So it can be concluded that there is an effect of the Student Centered Learning model on badminton playing skills, there is no influence of the Teacher Centered Learning model on badminton playing skills, and there is a difference in the effect of Teacher Centered Learning and Student Centered Learning on the badminton playing skills of SMPN 1 Waled students who take part in extracurricular activities. badminton. Keywords: Teacher Centered Learning, Student Centered Learning, Badminton